The Impact of Early Marriage: a Literature Review - Evita Rohmaniah; Iis Rahmawati; Muhamad Zulfatul A'la (Universitas Pahlawan Tuanku Tambusai, 2025)
Early marriage is not a new phenomenon that occurs in Indonesia or in other countries. The Statistics Center noted that the incidence or prevalence of early marriage is higher in rural areas with a figure of 27.11% compared to urban areas at 17.09%. The purpose of the study was to analyze the impact of early marriage in Indonesia, so as to obtain strategies and recommendations that have the potential to create positive changes in handling problems that lead to negative impacts on adolescents who marry at an early age. This research method uses Literature Review. The literature search process carried out in this literature review uses the database used in the article in the search for articles in the form of Google Scholar, Pubmed, and scient direct with a publication year range of 2018-2023. The search was carried out using several keywords